2018
DOI: 10.1002/open.201800029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Aza‐aromatic Curcuminoids with Improved Biological Activities towards Various Cancer Cell Lines

Abstract: Curcumin, a natural compound extracted from the rhizomes of Curcuma longa, displays pronounced anticancer properties but lacks good bioavailability and stability. In a previous study, we initiated structure modification of the curcumin scaffold by imination of the labile β‐diketone moiety to produce novel β‐enaminone derivatives. These compounds showed promising properties for elaborate follow‐up studies. In this work, we focused on another class of nitrogen‐containing curcuminoids with a similar objective: to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…Interestingly, compounds 3 c , e , h , l and 4 c even displayed comparable activity to the commercial doxorubicin drug. Previous work demonstrated that the introduction of azaheteroaromatic moieties leads to higher antiproliferative properties . Therefore, with the intention to combine antioxidant and antiproliferative properties, compounds 3–4 were designed in this work, and these compounds indeed showed an improved antiproliferative capacity, in addition to a better water solubility.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, compounds 3 c , e , h , l and 4 c even displayed comparable activity to the commercial doxorubicin drug. Previous work demonstrated that the introduction of azaheteroaromatic moieties leads to higher antiproliferative properties . Therefore, with the intention to combine antioxidant and antiproliferative properties, compounds 3–4 were designed in this work, and these compounds indeed showed an improved antiproliferative capacity, in addition to a better water solubility.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic procedure for the preparation of non‐symmetrical curcuminoids is based on previously reported optimized conditions for the synthesis of curcumin and symmetrical curcumin analogues ,. In this work, however, two consecutive condensation reactions with different aldehydes had to be executed in order to obtain the desired non‐symmetrical curcuminoids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations